Hyperoxia Induced Bronchopulmonary Dysplasia-Like Inflammation via miR34a-TNIP2-IL-1β Pathway - Tao, Xuwei; Mo, Luxia; Zeng, Lingkong (Frontiers in Pediatrics, 2022)
Lung injury induced by oxygen is a key contributor to the pathogenesis of preterm infant bronchopulmonary dysplasia (BPD). To date, there are comprehensive therapeutic strategy for this disease, but the underlying mechanism is still in progress. By using lentivirus, we constructed microRNA34a (miR34a)-overexpressing or knockdown A549 cell lines, and exposure to hyperoxia to mimic oxygen induce lung injury. In this study, we investigated 4 proinflammatory cytokines, interleukin-1β (IL-1β), tumor necrosis factor-α (TNF-α), angiopoietin-1 (Ang-1) and Cyclooxygenase-2 (COX-2) in the secreted sputum of infants who received mechanical ventilation, and found that IL-1β was substantially elevated in the first week after oxygen therapy and with no significant decrease until the fourth week, while TNF-α, Ang-1 and COX-2 were increased in the first week but decreased quickly in the following weeks. In addition, in vitro assay revealed that hyperoxia significantly increased the expression of miR-34a, which positively regulated the proinflammatory cytokine IL-1β in a time- and concentration-dependent manner in A549 cells. Overexpressing or knockdown miR34 would exacerbate or inhibit production of IL-1β and its upstream NOD-, LRR- and pyrin domain-containing protein 3 (NLRP3) inflammasome signaling pathway. Mechanically, it’s found that TNFAIP3 interacting protein 2 (TNIP2), an inhibitor of nuclear factor κB (NF-κB), is a direct target of miR34a, negatively regulated activation of NLRP3 inflammasome and the production of IL-1β. Overexpressing TNIP2 ameliorated hyperoxia-induced production of IL-1β and cell apoptosis. Our findings suggest that TNIP2 may be a potential clinical marker in the diagnosis of BPD.